Torsatron U-2M with reversed additional toroidal magnetic field - Kotenko, V.G.; Pavlichenko, R.O. (Вопросы атомной науки и техники, 2020)
The torsatron U-2M magnetic system is equipped with 16 additional toroidal magnetic field coils. Under normal operating conditions the toroidal field coils create an additional toroidal magnetic field B₀ the direction of which coincides with the direction of a toroidal magnetic field component b₀ generated by the torsatron helical coils on the circular axis of the torus. In the torsatron with reversed toroidal magnetic field (RTF) the toroidal field coils create an additional toroidal magnetic field B₀ᵣ of opposite direction. In this study the conditions for developing the magnetic surface configuration with spatial magnetic axis in the torsatron U-2M with RTF are found out and the magnetic surface configuration properties are investigated. Магнітна система торсатрона У-2М має в своєму складі 16 котушок додаткового тороїдального магнітного поля. У стандартному режимі котушки створюють додаткове тороїдальне магнітне поле, напрямок якого співпадає з напрямком тороїдальної компоненти магнітного поля, яке створюється гвинтовими обмотками на круговій осі тору. У торсатроні з оберненим додатковим тороїдальним полем (ОТП) ці котушки створюють магнітне поле протилежного напрямку. З допомогою уточненої розрахункової моделі з’ясовуються умови реалізації в торсатроні У-2М з ОТП конфігурації магнітних поверхонь з просторовою магнітною віссю та досліджуються її параметри. Магнитная система торсатрона У-2М содержит 16 катушек дополнительного тороидального магнитного поля. В стандартном режиме катушки создают дополнительное тороидальное магнитное поле, направление которого совпадает с направлением тороидальной компоненты магнитного поля, создаваемой винтовыми обмотками торсатрона на круговой оси тора. В торсатроне с обращенным дополнительным тороидальным магнитным полем (ОТП) эти катушки создают дополнительное тороидальное магнитное поле противоположного направления. C помощью уточненной расчетной модели выясняются условия реализации в торсатроне У-2М с ОТП конфигурации магнитных поверхностей с пространственной магнитной осью и исследуются ее параметры.